Second‐Generation Cryoballoon Ablation in the Setting of Lone Paroxysmal Atrial Fibrillation: Single Procedural Outcome at 12 Months. (22nd April 2016) - DE REGIBUS, VALENTINA; MUGNAI, GIACOMO; MORAN, DARRAGH; HÜNÜK, BURAK; STRÖKER, ERWIN; HACIOGLU, EBRU; RUGGIERO, DIEGO; COUTIÑO‐MORENO, HUGO ENRIQUE; TAKARADA, KEN; BRUGADA, PEDRO; DE ASMUNDIS, CARLO; CHIERCHIA, GIAN‐BATTISTA
Second‐Generation Cryoballoon Ablation: Background: Lone atrial fibrillation (LAF) develops in younger individuals without cardiovascular or pulmonary disease. As pulmonary vein isolation has been recognized as an optimal treatment for drug‐resistant atrial fibrillation, cryoballoon ablation with second‐generation balloon (CB‐A) may be an ideal solution for LAF patients. Objective: The aim of this study was to investigate acute success, periprocedural complications and outcome over a 12‐month follow‐up period in a cohort of patients having undergone PV isolation (PVI) for LAF using CB‐A technology. Methods: A total of 75 consecutive patients (50 male, mean age 47 ± 12 years) with a diagnosis of lone paroxysmal atrial fibrillation who underwent pulmonary vein isolation (PVI) by CB‐A from June 2012 were included. All patients underwent this procedure with the 28 mm CB‐A. A total of 299 PVs (100%) could be isolated with CB‐A alone. Results: The freedom from AF recurrence after a single procedure was 92% of patients during the entire 13‐month follow‐up. When considering a blanking period (BP) of 3 months, success rate was 93.3%. Transient phrenic nerve palsy (PNP) was the most frequent complication, occurring in 5.3% of individuals (4 patients); complete recovery was documented for all of these patients prior to hospital discharge. Conclusions: CB‐A is extremely effective in achieving PVI and affords freedom from AF at 13‐month follow‐up in 93% of young patients affected by drug‐resistant LPAF following a 3‐month BP. The most frequent complication observed was PNP, which reverted prior to discharge in all patients.